Fault-tolerant formation control of heterogeneous multi-agent systems with unknown inputs and external disturbances - Yandong Li; Yongan Liu; Ling Zhu; Yuan Guo (Scientific Reports)
Abstract This paper displays an optimal fault-tolerant formation control method, which is applied to a heterogeneous multi-agent system(HMAS) consisting of multiple uncrewed aerial vehicles (UAVs) and uncrewed ground vehicles (UGVs), solving the problem of UAVs and UGVs cooperative formation control under the partial loss of effectiveness and interruption faults. The system uses the Kronecker product to embed the UAVs system model and UGVs system model into the state-space equation, addressing the issue of inconsistent matrix dimensions between the UAVs and UGVs system models. Considering the fault-tolerant control problem of directed topology HMAS with actuator partial loss of effectiveness (PLOE) faults and interrupt faults, a control allocation algorithm that does not require controller reconstruction is introduced. Combining optimization theory with control allocation algorithms, a fault-tolerant controller that does not require solving the Hamilton-Jacob-Bellman equation is obtained. Further, introduce the controller into the formation control problem of leader-follower HMAS, and demonstrate the effectiveness of the proposed algorithm through the Lyapunov stability theory. The algorithm is applied to the heterogeneous MAS, compensating for actuator faults. Finally, simulations are carried out on a formation system of three UAVs and three UGVs to assess the effectiveness of the proposed protocol.